2009
DOI: 10.1523/jneurosci.3645-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Preparation to Inhibit a Response Complements Response Inhibition during Performance of a Stop-Signal Task

Abstract: Inhibition of inappropriate responses is an essential executive function needed for adaptation to changing environments. In stop-signal tasks, which are often used to investigate response inhibition, subjects make "go" responses while they prepare to stop at a suddenly given "stop" signal. However, the preparatory processes ongoing before response inhibition have rarely been investigated, and it remains unclear how the preparation contributes to response inhibition. In the present study, a stop-signal task was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
355
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(414 citation statements)
references
References 54 publications
48
355
2
2
Order By: Relevance
“…2011; Logan, 1981;Logan & Burkell, 1986;Ramautar et al, 2004) and when subjects are given signals that indicate that stop signals are likely (Chikazoe et al, 2009;Verbruggen & Logan, 2009c). This strategic slowing may be severe enough to subvert the experiment (Leotti & Wager, 2010), invalidating estimates of SSRT (Verbruggen et al, 2013).…”
Section: Control Strategies In the Stop-signal Taskmentioning
confidence: 99%
“…2011; Logan, 1981;Logan & Burkell, 1986;Ramautar et al, 2004) and when subjects are given signals that indicate that stop signals are likely (Chikazoe et al, 2009;Verbruggen & Logan, 2009c). This strategic slowing may be severe enough to subvert the experiment (Leotti & Wager, 2010), invalidating estimates of SSRT (Verbruggen et al, 2013).…”
Section: Control Strategies In the Stop-signal Taskmentioning
confidence: 99%
“…We focused on the first-level contrast correct no-go vs correct odd as indicator of successful inhibition without the confounding influences of attentional capture (Chikazoe et al, 2009b;Criaud and Boulinguez, 2013). For comparability purposes, we also calculated the following first-level contrasts: (i) correct no-go4baseline, (ii) incorrect nogo4baseline, (iii) correct odd4baseline, and (iv) correct no-go4incorrect no-go.…”
Section: Go/no-go Task and Analysismentioning
confidence: 99%
“…Current models of action suppression distinguish between reactive stopping, when subjects are required to inhibit an action in response to infrequent stimuli (Aron and Poldrack, 2006;Li et al, 2008) and proactive stopping, when subjects stand ready to inhibit forthcoming actions when necessary (Ballanger et al, 2009;Chikazoe et al, 2009). Functional magnetic resonance imaging (fMRI) studies have identified a prefrontal-subcortical network supporting both types of executive control processes, and established within this network the important involvement of the subthalamic nucleus (STN, Aron and Poldrack, 2006;Ballanger et al, 2009;Chikazoe et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…e l s e v i e r . c o m / l o c a t e / y n i m g Chikazoe et al, 2009;Frank et al, 2007;Jahfari et al, 2010;van Maanen et al, 2011).…”
Section: Introductionunclassified